2003
DOI: 10.1046/j.1570-7458.2003.00076.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated CO2 and temperature on development and consumption rates of Octotoma championi and O. scabripennis feeding on Lantana camara

Abstract: We carried out a factorial experiment to explore the effect of doubled CO2 concentration and a 3 °C temperature increase on the development of a complete generation of the beetles Octotoma championi Baly and O. scabripennis Guérin‐Méneville (Coleoptera: Chrysomelidae). These species are biological control agents of Lantana camara L. (Verbenaceae), with a leaf‐mining larval phase and free‐living, leaf‐chewing adults. Plants grown at elevated CO2 had enhanced above‐ground biomass, thicker leaves, reduced nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 38 publications
(45 reference statements)
0
26
0
Order By: Relevance
“…This would likely be partially attributable to interactive effects of climatic variables—for example, the combined effects of drought, temperature and atmospheric gas levels, which would alter life history traits for all trophic levels simultaneously. The natural inclusion of additional trophic levels would moderate the presented plant–herbivore–predator relationship through altered phenological and physiological timings [81,82]. Furthermore, the physiological responses to altered variables may differ between trophic levels to the same climatic alterations, raising inconsistencies across scenarios and timescales [83,84].…”
Section: Discussionmentioning
confidence: 99%
“…This would likely be partially attributable to interactive effects of climatic variables—for example, the combined effects of drought, temperature and atmospheric gas levels, which would alter life history traits for all trophic levels simultaneously. The natural inclusion of additional trophic levels would moderate the presented plant–herbivore–predator relationship through altered phenological and physiological timings [81,82]. Furthermore, the physiological responses to altered variables may differ between trophic levels to the same climatic alterations, raising inconsistencies across scenarios and timescales [83,84].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has suggested that elevated temperatures can increase feeding activity of biological control agents (Forno and Bourne, 1986), but can also alter control success by shifting the geographic ranges in which plants and insects experience suitable thermal minima and maxima (Lu et al, 2013;Allen et al, 2014). Although effects of CO 2 on biological control have received less attention, elevated CO 2 can increase endophagous larval success of some biological agents by counteracting warming-induced leaf loss (Johns et al, 2003). The current study, which uniquely tests how CO 2 and temperature influence biological control in the field, demonstrates that biological control efficacy can be sensitive to elevated CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite considerable evidence that plant-insect interactions may be sensitive to climate change, field experiments testing such effects on biological control remain rare. This lack of research is especially evident when considering combined effects of elevated temperature and CO 2 on plant-insect interactions and biological control (Zvereva and Kozlov, 2006;DeLucia et al, 2012), which can also be highly variable (Johns and Hughes, 2002;Veteli et al, 2002;Johns et al, 2003;Zvereva and Kozlov, 2006;DeLucia et al, 2012;Scherber et al, 2013), leading to cautions against broad interpretations of climate change effects from single-factor studies (Bale et al, 2002;DeLucia et al, 2012;Robinson et al, 2012). One useful model system for examining the impacts of climate change on biological control is the introduction of the lesser knapweed flower weevil (L. minutus Gyllenhall; Coleoptera: Curculionidae) to control diffuse knapweed (Centuarea diffusa Lam.).…”
Section: Introductionmentioning
confidence: 99%
“…First, the inclusion of an additional trophic level, (i.e., a predator of the herbivorous insect) could alter the plant-herbivorous insect trophic relationship (e.g., [32]) by changing the timing and extent of feeding or the development rate of the herbivorous insect. Second, all the parts of a plant may not respond to climate change variables on the same time scales and mobile herbivorous insects could therefore seek out and continue to consume plant tissues with high nutrient value (e.g., [35]). Third, many plant and herbivorous insect species may physiologically respond differently to identical climate manipulations (e.g., [40,65]), and therefore, changes in trophic relationships may not be consistent across all scenarios.…”
Section: Discussionmentioning
confidence: 99%